District Achievement Test (DAT) Scores of Grade III Learners in Esperanza District I Division of Sultan Kudarat - Jocelyn C. Lomongo (RIRAI Publisher, 2022)
The study’s goal was to determine the level of District Achievement Test (DAT) Scores of Grade III Learners of public elementary schools in Esperanza District I, Division of Sultan Kudarat. It also determined the relationship of learners’ study habits and teachers’ classroom management and teaching styles. Descriptive method of research using correlation analysis of the data was used. The study was conducted in the three schools in Esperanza District I such as Doroteo Pastor Memorial Elementary School, Saliao Elementary School and Sagasa Elementary School. A sample of 80 learners randomly chosen from the three schools were the respondents of the study. Survey questionnaire was utilized to gather the data on learners’ study habits and teachers’ classroom management and teaching styles. Data were analyzed and interpreted using the mean and Pearson’s r at 5% level of significance. Study revealed that learners had a high level of study habits. Teachers’ classroom management and teaching styles were all rated excellent. The District Achievement Test Scores of the three elementary schools were interpreted as satisfactory in Filipino and Makabayan subjects while the three core subjects such as English, Mathematics and Science were all interpreted as fair. Finally, only study habits had a significant relationship on the District Achievement Test (DAT) scores of the learners specifically in Filipino subject. Thus, it is finally concluded that high level of pupils’ study habits tends to improve their scores in District Achievement Test (DAT).